39. SURGICAL APPLICATION OF LUMBAR AND ABDOMINAL DRAINAGE IN THE TREATMENT OF POST-SURGICAL CEREBRAL SPINAL FLUID LEAKAGE (Vietnam Journal of Community Medicine, 2024)
Cerebrospinal fluid (CSF) leakage, a potential complication following neurosurgical or spinal surgeries, poses significant risks including central nervous system infections and low-pressure headaches. When conservative treatments fail to address persistent leaks, surgical interventions such as ventriculoperitoneal (VP) shunting or lumboperitoneal (LP) shunting are considered. While VP shunts are widely used, they can lead to complications such as intraventricular hemorrhage and seizures. LP shunts, on the other hand, avoid cranial invasion and related complications, making them a suitable alternative, especially in patients with non-dilated ventricles. This study evaluates the effectiveness of LP shunts in three cases of post-neurosurgical CSF leakage at Nhân Dân 115 Hospital between January and June 2024. All three patients, having undergone craniotomies for various brain tumors, exhibited persistent CSF leaks unresponsive to conservative treatments. The LP shunt was chosen as the surgical option, utilizing Spetzler-type systems with adjustable drainage pressure. Postoperative outcomes were favorable, with no reported complications such as infection or shunt malfunction. Symptoms resolved in all cases, and patients were discharged within seven days of surgery. These findings suggest that LP shunts can be an effective and safe treatment for CSF leaks following neurosurgical procedures, particularly in patients with non-dilated ventricles. Further research with larger cohorts and longer follow-up periods is recommended to better assess the long-term efficacy of this intervention.